The process of attraction of foreign direct investment in the economy of the country - Gutkevych, Svitlana; Riabenko, Vladyslav (My University, 2018)
International investment activity is connected with the spread of ties between countries; this is an important moment in the economic activity of countries. The aspects of boosting of investment activity and creation of conditions for attraction of foreign investments are considered. Some problems of investing in the world and Ukraine are determined. The goal of foreign investment is, as a rule, long-term activity outside the investor’s country in order to generate profits and increase investment to increase the effect of reinvestment. The implementation of the process of direct foreign investment is determined by the organization of this process outside the country of the investor. According to the analysis, depending on the investor’s ability to assign the results of investment – the policy of the recipient country is planned. One of the objectives of a foreign investor is reducing tax pressure by using a tax base in another country. The attraction of foreign investments in the economy is an objectively necessary process that contributes to the country’s economic development and contributes to the integration of the country’s economy into the world economy.
Keywords: international investment; foreign direct investment; economic development; international capital movement; problems; міжнародні інвестиції; прямі іноземні інвестиції; економічний розвиток; міжнародний рух капіталу; проблеми; кафедра міжнародної економіки